2012
DOI: 10.7763/ijet.2012.v4.439
|View full text |Cite
|
Sign up to set email alerts
|

Active Node Based Sensor Wireless Network for Energy Management

Abstract: Abstract-Nowadays electricity is the prime source of energy around the world for domestic and industrial applications. Our lifestyle revolves around electrical appliances and devices which make it a core necessity. However there is a shortage of this very important source of energy, especially in country like Pakistan where the overall life and building pattern is highly energy inefficient. Furthermore, energy prices soar due to different reasons; more building owners and operators are turning to energy manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…However, only relying on people's awareness and behaviour may not be an effective approach. Indeed, an experimental study (Rizvi et al, 2012) has shown that more than 30% energy saving was achieved immediately after installing a monitoring system in a residential household, but the percentage reduced to less than 4% one month later.…”
Section: Context and Problematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only relying on people's awareness and behaviour may not be an effective approach. Indeed, an experimental study (Rizvi et al, 2012) has shown that more than 30% energy saving was achieved immediately after installing a monitoring system in a residential household, but the percentage reduced to less than 4% one month later.…”
Section: Context and Problematicsmentioning
confidence: 99%
“…The success of "Pokemon" mobile application where there's no concrete thing to win, allows imagining an immersive game where the objective is to progressively reduce the building's consumption. Web technology and social networks addiction has to be used in a long-term strategy to avoid the rough fall of efficiency (30% to 4% of energy reduction after one month) observed in (Rizvi et al, 2012). Section 3.2 shows a fragmentation of industrial solutions and a real dispersion of adoption efficiency.…”
Section: Technologies Out Of the Buildingmentioning
confidence: 99%